Physicochemical properties of Diethanolamine-functionalized Si-MCM-41 - Ahmed, S. (Trans Tech Publications Ltd, 2014)
Si-MCM-41 was functionalized with 10-50wt loading of Diethanolamine (DEA) using impregnation method and characterized for their physicochemical properties using XRD, FTIR and HRTEM. Results show that the intensity of the diffraction peaks attributed to the finger-prints of Si- MCM-41 decreases with increased loading of DEA. The peaks assign to (110), (200), and (210) planes start to disappear at DEA loading as low as 10wt. FTIR spectra of DEA-Si-MCM-41 show presence of âN-H and âC-H peaks which confirms the functionalization of Si-MCM-41 with DEA. HRTEM micrographs of all samples clearly show the uniform hexagonal pore arrangement which proved the structural integrity of Si-MCM-41 even after functionalization with 50wt. Â© 2014 Trans Tech Publications, Switzerland.